Cancer pain management: recommendations from a Latin-American experts panel. (November 2017) - Escobar Alvarez, Yolanda; Agamez Insignares, Claudia; Ahumada Olea, Monica; Barajas, Olga; Calderillo, German; Calvache Guamán, Jenny Cecilia; Caponero, Ricardo; Cavenago Salazar, Benjamín A; Del Giglio, Auro; Pupo Araya, Ana Rocío; Villalobos-Valencia, Ricardo; Yepes Pérez, Andrés; et al.
Generating a consensus in the Latin-American region on cancer pain management is a current need. Thus a panel of Latin-American experts met in Madrid in March 2017 in order to review the published literature, discuss the best approach for cancer pain classification and evaluation and also make recommendations of pharmacological and nonpharmacological therapies for cancer pain management improvement in Latin-American countries. The result of that meeting is presented in this document. The experts participating were from Costa Rica, Mexico, Chile, Colombia, Peru, Brazil and Ecuador, and the project coordinator was from Spain.